The algorithm of modelizing of crack development in structural material - Матченко, Т.І.; Зубець, А.В.; Яворська, О.I.; Мінневалієва, Л.Г. (Proceedings of National Aviation University (archive), 2004)
The algorithm and method of modelizing of fatigue crack growth velocity of a small tone at the top of crack depending on cycle's forms of loading and way of loading was proposed.